Glyphosate-Induced Antagonism in Rapid Response Giant Ragweed (Ambrosia trifida). (17th November 2017) - Harre, Nick T.; Young, Julie M.; Young, Bryan G.
Abstract: Glyphosate application to the rapid-response (RR) biotype of glyphosate-resistant (GR) giant ragweed ensues in loss of foliage via rapid tissue death, thereby reducing glyphosate translocation. Experiments were performed to determine if this GR response, in contrast to a non-rapid response (NRR) GR biotype, results in antagonism of the selective herbicides atrazine, cloransulam, dicamba, lactofen, and topramezone. Application of glyphosate at 1, 680 g ae ha –1 in the greenhouse resulted in antagonism between all five selective herbicides for the RR biotype, whereas glyphosate applied at 420 g ha –1 was antagonistic only for cloransulam. Application of selective herbicides 2 d prior to glyphosate treatment avoided the antagonism observed in the RR biotype. In the field, glyphosate mixtures with dicamba and topramezone were antagonistic on the RR biotype across both 2015 and 2016 field seasons. Thus, the RR effectively reduces glyphosate efficacy but also has potential to diminish the activity of glyphosate mixtures with selective herbicides, and the degree of antagonism between these mixtures escalates at increasing glyphosate rates.